Radiocarbon measurements of foraminifera with the mini carbon dating system (MICADAS) at the Centro Nacional de Aceleradores - Guerra, Roberta; Santos, F. J.; Agulló García, Lidia; García-Tenorio, R. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2019)
Radiocarbon (14C) measurements of foraminifera are often challenging as their reliability and accuracy can be biased by several complicating factors. In this work, at the Centro Nacional de Aceleradores (CNA) in Seville, an automated setup with a Carbonate Handling System coupled with an automated graphitization system has been tested to investigate the potential for running samples of foraminiferal carbonate for AMS 14C dating of marine archives. The reproducibility of 14C ages for blanks and standard materials indicates that reliable 14C analyses are possible for carbonate samples with a 14C age up to 50,000 yr BP. With this automated procedure we were able to date monospecific planktonic foraminifera younger than 1000 yr BP. Biological mixing and high sedimentation are potentially complicating mechanisms resulting in anomalous young 14C ages in planktonic foraminifera from the deep Mediterranean Sea. The research leading to these results was supported by the European Science Foundation (ESF) Exchange Visit Grant 5103 ‘Dating and TIming of fluxes into and out of the MarinE CArbon Reservoir of the MeDiterranean Sea (TIMECARD)’ under the Research Networking Programme Earthtime – The European Contribution (EARTHTIME-EU). We are deeply indebted to Leonardo Langone from the CNR-ISMAR for providing the planktonic foraminifera samples along with numerous geochemical proxies used to interpret data from this study. Peer reviewed